How Much do Children Use the Second Implant when They Receive Sequential, Bilateral (Two) Cochlear Implants? - Cheu, Lih AW (2008)
To examine the patterns of second cochlear implant usage by children and adolescents in the two-year period following the receipt of the second implant. Design: This is a retrospective study examining the returned diaries (including reports by parents or teachers) of twenty-one children and adolescents who received a sequential second implant for two-year period from year 2004 to 2009, to describe the patterns of usage of devices: first implant, second implant and bilateral implants. The participants received their second implant between 2 years 1 month (2y1 m) and 19y3m {median age = 8y11 m). The time interval between implant ranged from 6m to 16y8m (median= 5y9m). Diaries of three children with simultaneous bilateral implants aged 9.1 mth, 9.3month and 1y9m were included to illustrate any potential differences from sequential bilateral implants. Results: Results show that the majority of the time (an average of 11 hours per day) participants with sequential implants used both implants together. The average use of the second cochlear implant was on average 21 minutes per day over the 24 months post switch-on compared with the usage of the first implant alone which was 1.3 hours per day. The mean hours of daily use of the second cochlear implant alone did not vary greatly across participants. Conclusions: The minimal usage of the second cochlear implant alone indicates that more counselling would be required by the clinician to increase its usage in children and adolescents with sequential cochlear implants. The importance of training the new cochlear implant alone should be highlighted in the rehabilitation program, in particular, during the first few months post switch-on of the new implant.